PENYULUHAN KESEHATAN TENTANG PENTINGNYA PERAWATAN PAYUDARA UNTUK MENINGKATKAN PRODUKSI ASI SEBAGAI PERSIAPAN MASA MENYUSUI PADA IBU HAMIL - laska, yulinda; Ikha Paramitha, Risma (Awal Bros Journal of Community Development, 2020)
During pregnancy, many pregnant women, especially primigravida, do not know the importance of breast care in preparation for breastfeeding, causing pregnant women to experience problems with their breasts and milk production during breastfeeding. This can happen because mothers are lazy or mothers who do not know the benefits of breast care during pregnancy. Breast care in pregnant women aims to increase milk production during breastfeeding. Community service activities that have been carried out are in the form of health counseling by providing materials related to breast care for pregnant women as a form of preparation for breastfeeding so that milk production can increase. The targets in this activity are pregnant women and postpartum mothers, midwifery students, especially midwifery students at STIKes Awal Bros Batam, health workers, especially midwives. Community service activities carried out by providing materials with the theme "The Importance of Breast Care in Pregnant Women" online through Zoom Cloud Meetings. This community service activity has been carried out on July 7, 2020. The benefits obtained from this community service activity include, among others, that participants gain knowledge about the importance of breast care for pregnant women. With this, the participants can use their knowledge of breast care as a skill that can be used for themselves and others.